Dietary derived compounds in cancer chemoprevention - Langner, Ewa; Rzeski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2012)
Cancer chemoprevention is defined as the application of natural or synthetic agents to suppress or reverse cancer development and progression. In this field especially diet derived compounds have recently attracted researchers’ attention as potential therapeutics generally exerting low toxicity compared with regular drugs. This review presents a survey of recent findings concerning the most promising dietary chemopreventive agents such as green tea polyphenols (i.e. catechins), long-chain polyunsaturated fatty acids, carotenoids, glucosinolates/isothiocyanates, vitamins (i.e. vitamin D and folate) and minerals (i.e. calcium and selenium). Molecular targets involved in intrinsic pathways affected by these natural compounds are also shortly discussed.